The Influence of Word Detective Strategy towards Students’ Vocabulary Mastery - Khoiriyah, Anisa Al; Zulianti , Hajjah; Hastomo, Tommy (IJLHE: International Journal of Language, Humanities, and Education, 2022)
The purpose of this research is to determine the influence of Word Detective Strategy towards students’ vocabulary mastery. The writer utilized a quasi-experimental method to conduct the research. The population of this research was the tenth grade students of SMK Negeri 7 Bandar Lampung. There were 473 students in 13 classes. The research sample consisted of two classes: an experimental class called X-AK1 and a control class called X-AK2. Cluster random sampling was applied by the writer in taking the sample. The writer utilized a multiple-choice test to measure the students' vocabulary mastery when collecting data. The writer utilized the sample t test formula to analyze the data. Students who were taught using the Word Detective Strategy scored higher than students who were taught using the Translation Technique, according to the data analysis. The average score of the experimental class was higher than the control class, according to the hypothesis testing calculation. The average score of the experimental class was 74.4 and the average score of the control class was 49.9. It may also be observed that t-test higher than t-table (t test > t table), that was 10.99>2.62 at the significance level 1% and 10.99>1.98 at the significance level 5%. Therefore, Word Detective Strategy had a positive impact on students’ vocabulary mastery at the tenth grade of SMK Negeri 7 Bandar Lampung in 2020/2021.